EVALUATION OF A SAFER MALE CIRCUMCISION TRAINING PROGRAMME FOR TRADITIONAL SURGEONS AND NURSES IN THE EASTERN CAPE, SOUTH AFRICA - Peltzer, Karl; Nqeketo, Ayanda; Petros, George; Kanta, Xola (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
Training designed to improve circumcision knowledge, attitude and practice was delivered over 5 days to 34 traditional surgeons and 49 traditional nurses in the Eastern Cape, South Africa. Training included the following topics: initiation rites; statutory regulation of traditional male circumcision and initiation into Manhood (TCIM); structure and function of the male sex organs; procedure of safe circumcision, infection control; sexually transmitted infections (STIs); HIV/AIDS; infection control measures; aftercare of the initiate including after care of the circumcision wound and initiate as a whole; detection and early management of common complications of circumcision; nutrition and fluid management; code of conduct and ethics; and sexual health education. The evaluation of the training consisted of a prospective assessment of knowledge and attitude immediately prior to and after training. Significant improvement in knowledge and/or attitudes was observed in legal aspects, STI, HIV and environmental aspects, attitudes in terms of improved collaboration with biomedical health care providers, normal and abnormal anatomy and physiology, sexually transmitted infections and including HIV, circumcision practice and aftercare of initiates. We concluded that safer circumcision training can be successfully delivered to traditional surgeons and nurses.